Retrospective cumulative dietary risk assessment of craniofacial alterations by residues of pesticides. (6th October 2022) - ,; Anagnostopoulos, Chris; Anastassiadou, Maria; Castoldi, Anna Federica; Cavelier, Adeline; Coja, Tamara; Crivellente, Federica; Dujardin, Bruno; Hart, Andy; Hooghe, Wim; Jarrah, Samira; Machera, Kyriaki; et al.
Abstract: EFSA established cumulative assessment groups and conducted retrospective cumulative risk assessments for two types of craniofacial alterations (alterations due to abnormal skeletal development, head soft tissue alterations and brain neural tube defects) for 14 European populations of women in childbearing age. Cumulative acute exposure calculations were performed by probabilistic modelling using monitoring data collected by Member States in 2017, 2018 and 2019. A rigorous uncertainty analysis was performed using expert knowledge elicitation. Considering all sources of uncertainty, their dependencies and differences between populations, it was concluded with varying degrees of certainty that the MOET resulting from cumulative exposure is above 100 for the two types of craniofacial alterations. The threshold for regulatory consideration established by risk managers is therefore not exceeded. Considering the severity of the effects under consideration, it was also assessed whether the MOET is above 500. This was the case with varying levels of certainty for the head soft tissue alterations and brain neural tube defects. However, for the alterations due to abnormal skeletal development, it was found about as likely as not that the MOET is above 500 in most populations. For two populations, it was even found more likely that the MOET is below 500. These results were discussed in the light of the conservatism of the methodological approach.